Correspondence and notes of Florence O'Donoghue during the course of his service as Intelligence Officer in the army during the Second World War, - O'Donoghue, Florence, 1895-1967 (1942)
Documents relate to appointments, promotions, courts of inquiry and other army matters, with some intelligence communications. Includes a pamphlet titled 'Police Persecution of Patriot Family' relating to the family of Tomás MacCurtain.